Acidity, pH and Viscosity of Red Dragon Fruit Yoghurt with The Addition of Some Levels of Sucrose - Zainur Rohman; Novita Hindratiningrum; Siti Rahmawati Zulaikhah (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2022)
The purpose of this study was to determine the effect of the level of addition of sucrose on the characteristics (acidity, pH, and viscosity) of red dragon fruit yoghurt. This research was carried out using an experimental method with a completely randomized design (CRD) using 4 treatments and 5 replications. The treatment in this study was the addition of various levels of sucrose (5 %, 10 %, 15 %, 20 % (w/v)). The variables observed were the level of acidity, pH, and viscosity of red dragon fruit yoghurt. The results showed that the addition of various levels of sucrose affects the acidity of the yoghurt which tends to decrease, the pH of the yoghurt tends to increase and the viscosity of the yoghurt was decreasing.